Preferred identity as phoenix epiphanies for people immersed in their illness experiences. A qualitative study on autobiographies - Natascia Bobbo (University of Bologna, 2021)
The illness immersion condition prevents patients from enjoying everything worth living life for. In any case, according to Frank, this condition could represent one of the most insightful experiences towards understanding the meaning of life. Using the metaphor of phoenix (as a symbol of rebirth) taken from May (1991), Frank identified four kinds of embodiments through which the phoenix can reveal itself in a patient after an illness immersion experience: the phoenix that could ever be and the phoenix that might have been; the recurrent and cumulative phoenix and the reluctant phoenix. Based on these considerations, a qualitative study was conducted in order to give voice to the different phoenix embodiments focusing on several autobiographies of patients afflicted with severe or terminal illness. The analysis highlights several similarities that the different phoenixes shared (i.e. the ability to use words and experiential learning skill); however, a deep difference emerged in their worldview which proves able to lead them towards different epiphanies. These evidences reveal that every sick person should be understood, stimulated and accompanied throughout his lived experience of illness by an expressly designed and dedicated care.